2016
DOI: 10.1039/c5sm00707k
|View full text |Cite
|
Sign up to set email alerts
|

A soft biomolecule actuator based on a highly functionalized bacterial cellulose nano-fiber network with carboxylic acid groups

Abstract: PSS layers were deposited on both sides of the CBC-IL membranes by a dip-coating technique to yield a sandwiched actuator system. Ionic conductivity and ionic exchange capacity of the CBC membrane can be increased up to 22.8 times and 1.5 times compared with pristine bacterial cellulose (BC), respectively, resulting in 8 times large bending deformation than the pure BC actuators with metallic electrodes in an open air environment. The developed CBC-IL actuators show significant progress in the development of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…17,18,21,33 Briefly, BC (1 g) was immersed in deionized water (100ml) under gentle stirring at room temperature. 17,18,21,33 Briefly, BC (1 g) was immersed in deionized water (100ml) under gentle stirring at room temperature.…”
Section: Preparation Of Cbcmentioning
confidence: 99%
See 4 more Smart Citations
“…17,18,21,33 Briefly, BC (1 g) was immersed in deionized water (100ml) under gentle stirring at room temperature. 17,18,21,33 Briefly, BC (1 g) was immersed in deionized water (100ml) under gentle stirring at room temperature.…”
Section: Preparation Of Cbcmentioning
confidence: 99%
“…It is clearly observed that the bending tip displacement of CBC-IL actuator could be enhanced by the addition of small amount of PAMPS. 6,9,12,14,17,39,40 Furthermore, the actuation durability of the CBC-IL-PAMPS biocomposite actuator was investigated, as shown in Fig. Furthermore, relaxation behavior was not found in the biocomposite actuators due to many weaklypolar carboxylate functional groups present within the CBC-IL-PAMPS composite membrane matrix.…”
Section: Actuation Performancesmentioning
confidence: 99%
See 3 more Smart Citations